PEMANFAATAN MEDIA POP-UP BOOK UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA MATERI RAGAM BENTANG ALAM KELAS IV SDN 14/I SUNGAI BAUNG - Saputri, Irma Armelia; Chan, Faizal; Khoirunnisa, Khoirunnisa (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the utilization of Pop-Up Book media on the topic of diverse landforms to enhance the learning engagement of fourth-grade elementary school students. The research method used is Classroom Action Research, with the subjects consisting of the classroom teacher and all 20 fourth-grade students of SDN 14/I Sungai Baung, including 9 boys and 11 girls. Data collection techniques included observation and interviews. Source triangulation and technique triangulation were employed to ensure the accuracy of the data regarding the use of Pop-Up Book media in the learning activities. Student learning engagement data were analyzed both qualitatively and quantitatively. The results of the study indicate an increase in student learning engagement following the implementation of the Pop-Up Book media. In the second cycle, the success criteria expected by the researcher were met, with a result of 74%. Thus, the intervention using Pop-Up Book media was successful in increasing student learning engagement.